Self regulated learning and motivation of Islamic studies and non-Islamic studies stream students - Mohamad Azrien, M.A.; Shukeri, M.; Sharifah, B.; Arifin, M. (2014)
Self-regulated learning and motivation is important aspects of students’ learning and academic performance in a classroom context. This study aims at 1) investigating the differences in selfregulated learning and motivation between the Islamic studies and non-Islamic studies stream students; 2) examining relationships between self-regulated learning, motivation and academic performance. Eight hundred and twenty five universities students were involved in this study. A self-report measure of students metacognitive self-regulation, help seeking, organization, effort regulation, self-efficacy, intrinsic and extrinsic goal orientation, task value and test anxiety was administered, and academic performance data were obtained from students’ cumulative grade point average (CGPA). The study uses a questionnaire as the informationgathering instrument. The questionnaire was based on the Motivated Strategies for Learning Questionnaire (MSLQ). T-test results indicated that students from Islamic studies background prefer using more strategies to score extrinsic goal orientation than non-Islamic studies students, and conversely, non-Islamic studies students practice metacognitive self-regulation strategies and organization strategies more than Islamic studies students did. Correlation analysis revealed that self-efficacy, intrinsic and extrinsic goal orientation, task value and test anxiety were positively related to metacognitive self-regulation, help seeking and organization. Regression analyses showed that test anxiety and intrinsic goal orientation appeared as the best predictors of academic performance.